Gender-specific associations between quality of life and leukocyte telomere length. (January 2018) - Choi, Eun Sil; Chang, Yu Kyung; Lee, Dong Hee; Ko, Jae-Hong; Lim, Inja; Bang, Hyoweon; Kim, Jung-Ha
Highlights: Leukocyte telomere length is associated with quality of life in Korean men and women aged 55 and over. The association between leukocyte telomere length and quality of life is gender-specific. Leukocyte telomere length is associated with physical quality of life in men and mental quality of life in women. Abstract: We conducted a study on the relationship between leukocyte telomere length (LTL) and quality of life (QoL) in 82 couples aged 55 and older. LTL was measured by quantitative real-time PCR. QoL was evaluated using the physical component score (PCS) and mental component score (MCS) on the Korean version of the Short-Form Health Survey (SF-36). LTL was found to be independently associated with the SF-36 PCS in males (β = 0.014, p = 0.03) and the SF-36 MCS in females (β = 1.16, p < 0.01). Thus LTL is associated with QoL in gender-specific ways.